The Challenge of Islamic Economics: by Muhammad Akram Khan Published by the All-Pakistan Islamic Education Congress, Lahore, 1986, 93 pages. $3.00 (American Journal of Islam and Society, 1986)
Muhammad Akram Khan, the well-known Islamic economist, is presentlyDirector-General in the Audit and Accounts Services of the government ofPakistan. He is a prolific writer and scholar with Islamic inspiration and astrong grip on the subject. He has written dozens of articles and books onIslamic economics since 1965 in English and Urdu. His works have beenpublished by organizations and journals of national and international repute.Two of his very important works are “Economic Teachings of ProphetMuhammad (PBUH)” and “Islamic Economics: Annotated Sources in Englishand Urdu.” The first book is a classified compilation of ahadith relating toIslamic economics and is being published by the Islamic Research Academy,Lahore. It is a monumental work that may turn out to be an indispensablereference on Islamic economics. The second book contains 1,300 abstractsclassified into approximately forty headings. It is the first annotatedbibliography on Islamic economics.“The Challenge of Islamic Economics,” the book under review, is madeup of three papers written, respectively, for the “Journal of Research in IslamicEconomics” in 1983, “the Third International Seminar on Islamic Thought,”held under the auspices of the International Institute of Islamic Thought inKuala Lumpur in July 1984, and the “International Seminar on IslamicEconomics” held at Sokoto in February 1985. They make up chapters one,two, and three respectively.The book is addressed to the teachers and researchers in Islamiceconomics. It informs its readers of the nature, scope, and methodology ofthis discipline. It points out some of the strengths and weaknesses in theliteratme dealing with this subject and advances an approach for teachingIslamic economics. This book, like most of the author‘s writings, is logical,consistent, and thought--provoking ...